Evaluasi Hasil Pembangunan Penampungan Air Minum Masyarakat Desa Silima Banua Umbunasi Kecamatan Ulu Idanotae Kabupaten Nias Selatan - Sheila Hani; Rini Rini; Ridwan Nasution; Luther Setiawan (Majalah Ilmiah METHODA, 2024)
Access to clean water in Silima Banua Village is a quite complex problem. The government then carried out construction of community drinking water reservoirs. After construction was completed, research was carried out on drinking water reservoirs. This research examines the impact of the construction of drinking water reservoirs on the availability of clean water, public health and the quality of infrastructure in Silimabanua Umbunasi Village, South Nias Regency. Data was collected through surveys, interviews, and field observations to analyze changes in access to clean water before and after development, its impact on public health, and the physical quality of water reservoirs. The research results show a significant increase in the availability of clean water after construction, which positively affects public health. Apart from that, the physical quality of the water reservoir is assessed as meeting established standards. Community participation, local government support, and drinking water quality were also identified as important factors in the success of this project.